Occipitosacral Fusion for Multiple Vertebral Fractures with Kyphotic Deformity in a Patient with Mutilating Rheumatoid Arthritis: A Case Report - Tanouchi, Tetsu; Shimizu, Takachika; Ino, Masatake; Toda, Naofumi; Manabe, Nodoka; Itoh, Kanako; Fueki, Keisuke (The Surgery Journal, 2017)
Osteoporotic vertebral fractures are well-known complications of rheumatoid arthritis. The management of multiple vertebral fractures with kyphotic deformity is controversial. We present a case of a patient with mutilating rheumatoid arthritis who had multiple vertebral fractures with kyphotic deformity after occipitothoracic fusion for rheumatoid cervical disorder. Occipitosacral fusion was effective to create stable spine with better sagittal alignment in this case, but careful clinical assessment for early detection and management of postoperative insufficient pelvic fracture were required.
Keywords: Kyphosis; osteoporosis; rheumatoid arthritis; thoracolumbar spine; vertebral compression fracture